UNDERSTANDING TERRORISM CONCEPTS, THEORIES, AND CAUSES - Esmailzadeh, Yaser (Gerakbudaya Enterprise, 2023)
Terrorism is a relentless phenomenon that continues to haunt the human race, affecting societies across the world. While the world continues to interconnect with one another, terrorism too, continues to evolve, adapting to the changing contours of political, social, and economic landscapes. This book focuses on the political, economic, psychological, social, and cultural factors that underpin terrorism, shedding light on the conditions and motivations that give rise to such acts. As such, the book aims to equip readers with the necessary knowledge and tools to comprehend this complex phenomenon, as well as providing the necessary knowledge to contribute to informed debates on counter-terrorism. The case studies that are written in this book will help readers understand the complex dynamics at play, as well as the many different concepts of terrorism itself. With this, it is with hope that future generations may use this book as a basis to explore the potential emergence of other waves of terrorism, and to develop advanced prospects for effective counterterrorism in the face of these evolving challenges.